2000
DOI: 10.4049/jimmunol.165.9.5245
|View full text |Cite
|
Sign up to set email alerts
|

IL-1β Converting Enzyme Is a Target for Nitric Oxide-Releasing Aspirin: New Insights in the Antiinflammatory Mechanism of Nitric Oxide-Releasing Nonsteroidal Antiinflammatory Drugs

Abstract: Caspase-1, the IL-1β converting enzyme (ICE), is required for intracellular processing/maturation of IL-1β and IL-18. NO releasing nonsteroidal antiinflammatory drugs (NSAIDs) are a new class of NSAID derivatives that spare the gastric mucosa. Here, we tested the hypothesis that NCX-4016, a NO-aspirin derivative, inhibits proinflammatory cytokine release from endotoxin (LPS)-challenged monocytes. Our results demonstrated that exposing LPS-stimulated human monocytes to NCX-4016 resulted in a 40–80% inhibition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
86
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(91 citation statements)
references
References 53 publications
5
86
0
Order By: Relevance
“…Additional evidence is given by the reduction in the antiaggregatory activity of NCX4106 in the presence of oxyhaemoglobin, a NO scavenger, or methylene blue (Lechi et al, 1996). Con®rming previous studies, we found that intracellular cyclic GMP is increased in adherent human monocytes up to 6 h after incubation with NCX4016 (Fiorucci et al, 2000b). The absence of any increase in this NO-induced intracellular signal may explain the reduction in NCX4016 activity after more prolonged incubation.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Additional evidence is given by the reduction in the antiaggregatory activity of NCX4106 in the presence of oxyhaemoglobin, a NO scavenger, or methylene blue (Lechi et al, 1996). Con®rming previous studies, we found that intracellular cyclic GMP is increased in adherent human monocytes up to 6 h after incubation with NCX4016 (Fiorucci et al, 2000b). The absence of any increase in this NO-induced intracellular signal may explain the reduction in NCX4016 activity after more prolonged incubation.…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, NCX4017 which is similar to NCX4017 but is deprived of the NO-releasing moiety, dose-dependently decreases TXB 2 generation. It is worth noting that NCX4017 was shown to be cytotoxic in human monocytes after prolonged incubation, but this is not observed after a 6-h incubation period (Fiorucci et al, 2000b). In all the conditions where NO activity is prevented, NCX4016 proves less eective than ASA.…”
Section: Discussionmentioning
confidence: 92%
“…The drug has been shown to release sustained amounts of NO in vivo (14,15). Although the use of NSAIDs is limited by their gastrointestinal (GI) and renal toxicity, NOreleasing NSAIDs were shown to exert antiinflammatory and analgesic effects that were at least as potent as those of the parent drug, without causing GI tract toxicity (16)(17)(18)(19). The in vivo metabolism of these drugs has been established reasonably well in a rat model (14,20), except that the precise mechanism by which NO is released from the nitro moiety has yet to be understood.…”
Section: Effect Of Ncx-4016 On the Clonogenecity Of Hoccsmentioning
confidence: 99%
“…Coupling of a NO-releasing moiety to conventional nonsteroidal antiinflammatory drugs or other antiinflammatory drugs was attempted to reduce the gastrointestinal toxicity of these compounds (18). These new molecules have interesting properties, such as antioxidant activity, suppression of reactive oxygen species generation (19), inhibition of proinflammatory cytokine release by mononuclear cells (20), feedback inhibition of NOS2 catalytic activity (21), and suppression of cancer cell proliferation (22), all of which make them attractive and safe candidates for alleviating MSC-induced alterations of the immune system in tumor-bearing hosts. 13.…”
mentioning
confidence: 99%